Thunderbird Country Club advertisement, The Villager: Palm Springs Magazine, 1957 (1957)
Issue of "The Villager: The magazine of Fine Desert Living," October 1957 featuring Thunderbird Country Club and Frank Sinatra's home at the Tamarisk Country Club.